2017
DOI: 10.1080/09638288.2017.1366555
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural validation of the Falls Efficacy Scale-International to assess concerns about falls among Hungarian community-living older people

Abstract: Translation and cultural adaptation of the original scale were successful. The Hungarian version proved to be a reliable, valid tool confirming that it can be used in future clinical and scientific work with Hungarian older people. Implications for rehabilitation Excessive concerns about falls may lead to avoidance of activities, decreasing functional abilities, increasing of risk of a future fall, ultimately premature nursing home admission. The Falls Efficacy Scale-International is a widespread tool for asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
2
8
1
2
Order By: Relevance
“…(35,36) FES-I, in turn, is based on the Social Cognitive Theory, which presents excellent psychometric properties, with a 96% internal consistency. 37) This scale is widely used and has already been validated in several countries, such as Brazil, (38) Portugal, (39) Saudi Arabia, (40) Turkey (41) and Spain. (42) These authors point out that tools that measure fall self-efficacy are used to measure fear of falling and vice versa, besides that, there are tools that measure two distinct constructs (fall self-efficacy and fear of falling), as a single construct (fear of falling) in this way, it is still unclear what is the best scale to measure fear of falling.…”
Section: Discussionmentioning
confidence: 99%
“…(35,36) FES-I, in turn, is based on the Social Cognitive Theory, which presents excellent psychometric properties, with a 96% internal consistency. 37) This scale is widely used and has already been validated in several countries, such as Brazil, (38) Portugal, (39) Saudi Arabia, (40) Turkey (41) and Spain. (42) These authors point out that tools that measure fall self-efficacy are used to measure fear of falling and vice versa, besides that, there are tools that measure two distinct constructs (fall self-efficacy and fear of falling), as a single construct (fear of falling) in this way, it is still unclear what is the best scale to measure fear of falling.…”
Section: Discussionmentioning
confidence: 99%
“…Three items listed under factor 2 were the same across cultures (i.e., 11: walking on a slippery surface; 14: walking on an uneven surface; and 15: walking up or down a slope). The common characteristic was ambulation on a difficult/dangerous terrain [5, 8, 10, 11, 15, 30]. For items in factor 2, which were listed solely in our study, the common denominator was social inclusion (i.e., 10: a brisk walk to a ringing phone; 12: visiting friends; and 16: going to a social event).…”
Section: Discussionmentioning
confidence: 99%
“…It was developed and validated by the Prevention of Falls Network Europe [5, 6]. Previous studies have shown that the FES-I is a valid and reliable test for assessing an FoF in older adults across cultural environments [7, 8, 9, 10, 11, 12, 13, 14, 15, 16]. Validation studies for the FES-I have been carried out in different older patient groups, such as community-dwelling older people [15], users of older people's day centers [17], and hospitalized older adults [18]; however, only a few studies have analyzed the characteristics of persons with cognitive impairment [19].…”
Section: Introductionmentioning
confidence: 99%
“…A total score of 7-8 was classified as little or no fear of falling, 9-13 as moderate fear of falling, and 14 or more as severe fear of falling (Delbaere et al, 2010). The Cronbach alpha coefficient of test-retest reliability for the Short FES-I has been reported as 0.93 (Kovács et al, 2018). Preintervention and postintervention evaluations were performed by the same investigator and were conducted through one-on-one interviews with the subjects.…”
Section: Outcome Measuresmentioning
confidence: 99%